Characterization of shaleâs sweet-spots - Prajapati, S. (European Association of Geoscientists and Engineers, EAGE, 2021)
This study draws together pre-stack inversion, basic rock physics analysis, and well-log to discuss how to identify and characterize the shale âsweet-spotsâ. First, consider the influence parameters to model the amplitude variation with offset (AVO) synthetic results to explain the shale characteristics. Then using elastic inversion results imposed on well-log data to separate the Shale and Sand reservoir. The results show that velocity and Poisson ratio are the most sensitive elastic parameters to indicate the lithologic properties of sweet spot in tight sandstone reservoir. The P-impedance and porosity relationship clearly explain the shale characteristics and discriminate with the other lithological properties. Such kind of study open the possibility and opportunity to understand about shale fracture reservoir, as shale itself contain an anisotropy behavior with extremely low permeability. Â© EAGE Asia Pacific Virtual Geoscience Week 2021. All rights reserved.